The Relationship Between Emotion Regulation and Aggressiveness in Grade VI Elementary School Students: Hubungan Antara Regulasi Emosi Dengan Agresivitas Pada Siswa Kelas VI Sekolah Dasar - Nabila Kairina Maskuri; Ghozali Rusyid Affandi (Universitas Muhammadiyah Sidoarjo, 2021)
This research was conducted because of the phenomenon of aggressiveness that emerged in SDN Kludan. The purpose of this study was to determine the relationship between emotional regulation and aggressiveness in grade VI SDN Kludan students. The hypothesis proposed is that there is a negative relationship between emotional regulation and aggressiveness in elementary students. The variables of this study were emotion regulation as the independent variable and aggressiveness as the dependent variable. The population in this study were 120 students. The sampling technique used is saturated sampling technique. Data analysis used the Pearson Product Moment Correlation statistical technique with the help of SPSS 16.0 for windows. The results of the analysis show a correlation coefficient of -0.763 with a significance value of - .001 <0.05. It is concluded that the hypothesis proposed in this study is accepted, that is, there is a negative relationship between emotional regulation and aggressiveness. meaning that the higher the emotional regulation, the lower the aggressiveness, and vice versa, the lower the emotional regulation, the higher the aggressiveness. Keywords: Emotion Regulation; Aggressiveness; Elementary School Students; Class VI